Managerial Culture in Sports Organizations in Kosovo as a Factor in the Integration in International Sports Associations - Gani Ibrahimi; Florian Miftari (Kazimierz Wielki University, 2019)
This topic is relevant due to the lack of systematic research and knowledge about leadership, management and the organizational culture in sport organizations in Kosovo after their integration in international sport organizations. The interest in studying organizational structures resides in the relationship between organizational design and other organizational phenomena like performance, distribution of power, or control systems. While there is plenty of literature on organizational structure studying different types of organizations, little is written in books and journals on the specific field of sport organizations in Kosovo. The object of research is the organizational culture and management of sport institutions in Kosovo. The subject of research is the impact of integration processes in the international sport organisations in the, regulatory and administrative changes on the organizational culture of the sport institutions environment in Kosovo. Tasks of the study: • To analyze the existing knowledge on the subject which is completely missing and to formulate questions that should be given a scientifically sound answer; • To adapt the method of measuring and evaluating the type of organizational culture (Cameron and Quinn) to the conditions of sport organizations in Kosovo; • To develop and implement the methodology for diagnosing organizational culture in the sport organizations in Kosovo; • To conduct empirical research and to obtain new knowledge of the organizational culture in the sport organizations in Kosovo. • To assess the state of the organizational environment in the sport organizations in Kosovo and its influence on organizational culture; • To formulate conclusions and recommendations for forming and maintaining the desired profile of organizational culture that is necessary for the successful functioning of the Universities in Prishtina. The working hypothesis of the study is that there is still enough space to implement a new leadership style in sports organizations in Kosovo in order to achieve a higher efficiency within those institutions. The methodology of the study is based on the known method of evaluating and measuring organizational culture given by Kim Cameron and Robert Quinn and which has proved effective. The main methods used are: questionnaires, interviews, study of documents, observation and statistical processing of data obtained and provide reliable scientific results. Besides these methods, cultural anthropological interpretations, systematic description, expert analysis and benchmarking are also used. The final research product is new knowledge about the sport organizations environment in Kosovo and a profile of their organizational culture that can serve as a basis for management decisions.